Mengelola Denda dari Kasus Korupsi untuk Meningkatkan Pemulihan Aset Negara: Studi Kasus pada Komisi Pemberantasan Korupsi (KPK) - Nurul Hudaeini; Wati, Lela Nurlaela; Ramdany (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
The management of fines (penalties in the form of money) resulting from corruption cases is a critical issue at Indonesia's Corruption Eradication Commission (KPK), due to a decline in asset recovery achievements from 2017 to 2019, which has hindered the effective recovery of state financial losses. As an independent institution mandated to encounter corruption, KPK is responsible for enforcing court-ordered fines and compensation payments. However, administrative and execution challenges have prevented the KPK from meeting its asset recovery targets, highlighting the need for more effective and efficient fine management strategies. This study employs a qualitative methodology with an exploratory and normative juridical approach. Data were collected through observation and in-depth interviews with KPK policymakers directly involved in asset recovery and document analysis. The findings identify six key strategies to improve fines management: developing an integrated application system, optimizing the authority of execution prosecutors, incorporating fine execution performance into key performance indicators, seizing assets held by third parties, revising standard operating procedures, and strengthening asset blocking mechanisms. Implementing these strategies is expected to enhance KPK’s effectiveness in recovering state assets through improved management of corruption-related fines.